External Financing Patterns for Small and Medium Firms in Eastern Europe and Central Asia: Does Financial and Institutional Development Matter? - PORUMBOIU, Octavian (Journal of Advanced Studies in Finance, 2016)
This paper examines the financing patterns of small and medium firms in Eastern Europe and Central Asia transition region and the extent to which these patterns are influenced by financial and institutional development. Using recent firm-level data from 28 countries from the region, we analyse four external sources of financing of firms’ working capital and investments in fixed assets (i.e. financing from banks, nonbank financial institutions, suppliers and informal financing). While there are significant differences on the one hand between financing of working capital and financing of investments, and on the other hand across countries in terms of small firms’ financing patterns but also in terms of macroeconomic indicators, three findings stand out. First, our results suggest that small firms have less access to formal financing sources such as banks than medium and large firms. Second, financial development is shown to reduce small firms’ use of informal financing of both their working capital and investments and also to expand financing of their working capital from non-bank financial intermediaries. Third, better protection of property rights – as an indicator of institutional development – increases small firms’ access to finance from nonbank financial intermediaries.
Keywords: financial development, SMEs, financing patterns, Eastern Europe and Central Asia